La fonction de l’éditeur-auteur dans les éditions critiques numériques - Joana Casenave (Humanités Numériques)
This article studies the features of the editor-author function specific to scholarly editions, as well as the evolution of this function in digital scholarly editions. The advent of digital editions introduces a collective authorial body, which we analyse here. The evolution of the author function also deeply renews the way information becomes a discourse, both in its form and in the choice or the hierarchy of the contents made available. At the same time this modifies the process by which the authority of an edition is recognised, as well as the modalities of its scientific evaluation. This article thus explores the changes of the critical edition in the digital field.